[PP.26.20] ABPM PROFILES IN VERY ELDERLY SUBJECTS. (September 2017) - Agrati, A.; Colombo, F.; Ferraro, G.
Abstract : Objective: Ambulatory blood pressure monitoring (ABPM) is being increasingly used in the assessment of hypertension in all age groups, confirming the continuous relationship between blood pressure (BP) and cardiovascular (CV) risk amongst older people. Moreover, ABPM seems to be is a more accurate predictor of CV morbidity and mortality than isolated clinic measurements, providing a better estimate of BP load and the identification of white-coat hypertension, a known common phenomenon in the elderly. Design and method: 466 ABPMs of subjects aged 80 and over, referred at our Institution in the period 2000- 2016 were analyzed; all the recordings were performed using the same oscillometric device (TM 2430), All the usual ABPM parameters were recorded: mean 24 h systolic (MSP) and diastolic (MDP) pressures, pulse pressure (PP), blood pressure variability (BPV), dipping status and heart rate, clinical BP measurements, age, sex, body mass index, smoking habits, diabetes. Moreover dipper and non dipper status, post prandial fall were also calculated for all the pressures. Morning surge phenomenon was also taken into account Results: Considering ABPMs and clinical measurements, patients could be divided in different groups: normotensives (16%), white coat (34%), masked (1%), isolated systolic (33%), systo-diastolic (15%) and diastolic isolated (1%) hypertensives. In every group we also evaluated dipper status, post prandial BP falls, daily hypotensions (BP < 99/60 mmHg) more or less symptomatic and no significative differences were recorded in these latter parameters. Conclusions: 24hour ABPM provides many measurements for better analysis and proves to be a more accurate predictor of target organ damage and CV risk. This tool seems to be of a certain importance even in the better evaluation of elderly subjects and in their possible therapeutic approach. Non invasive ABPM can be a useful tool to help identify very elderly patients, considered at particularly high cardiovascular risk; Of course we must stress that our study population is not representative of the general population of elderly patients because outpatients over 80 years, by definition, are elderly in very good physical condition